KETAHANAN BANGUNAN RUMAH SAKIT TERHADAP BENCANA GEMPA BUMI DI BANTUL DAERAH ISTIMEWA YOGYAKARTA - Dhani Gesha Gutama; Rita Laksmitasari Rahayu (Lakar: Jurnal Arsitektur, 2021)
Earthquake-resistant buildings are an absolute necessity for the people of Indonesia, because they are prone to the risk of earthquake disasters. Judging from the history of earthquakes in Indonesia, every year there will always be a lot of victims and quite large losses. Therefore, it is necessary to understand the concept of earthquake resistant buildings in the community as well as to building construction experts. One of the important buildings that must consider the concept of earthquake-resistant building resilience is the hospital, this is because the hospital is an important institution that is engaged in individual health services that provide inpatient, outpatient and emergency care. When a natural disaster occurs, the role of a hospital is very important to provide intensive care to victims in a timely and good quality manner to minimize deaths. The city of Yogyakarta, especially in Bantul, is one of the places where there was an earthquake which caused the buildings in Bantul to collapse and caused considerable losses, property, buildings and infrastructure. After approximately 14 years have passed since the earthquake occurred, Bantul Regency has slowly revived with its construction, the buildings in Bantul Regency are slowly starting to return to normal, one of which is the Hospital. The resilience concept of earthquake-resistant buildings can be used as a supporting tool to increase the resilience index of systems, such as health care facilities, and reduce the vulnerability and consequences of earthquake disasters.